Barriers and facilitators to physical activity in men with prostate cancer: A qualitative and quantitative systematic review. Issue 12 (6th November 2019) - Fox, Louis; Wiseman, Theresa; Cahill, Declan; Beyer, Katharina; Peat, Nicola; Rammant, Elke; Van Hemelrijck, Mieke
Abstract: Objective: Existing research indicates that moderate‐to‐vigorous physical activity (PA) alleviates treatment side effects and is associated with survival in men with prostate cancer. We aimed to ascertain the state of research investigating barriers and facilitators to PA in men with prostate cancer and synthesise existing qualitative research on this topic. Methods: A systematic review of qualitative and quantitative studies was conducted. MEDLINE, Embase, PsycINFO, Web of Knowledge, CINAHL, PEDro, OATD, and WorldCat were searched to June 2019 for quantitative studies investigating causes or predictors of PA or qualitative studies describing patient‐reported barriers/facilitators to PA, amongst men with prostate cancer of any stage. Thirty‐two studies (n = 17 quantitative; n = 15 qualitative) were included from 3698 screened articles. Results: Heterogeneity and unsystematic reporting of quantitative study methods prohibited a quantitative data synthesis. Thematic synthesis of qualitative studies produced five analytical themes: individual needs by treatment pathway, self‐determination and its relationship with prostate cancer‐related events, co‐ordination and support of the clinical care team, individual preferences in discrete aspects of PA engagement style, and the potential for a bidirectional facilitative relationship between structured group PA and spontaneous peer support. Both qualitative and quantitative studies indicated incontinence as a barrier. Conclusions: Unsystematic reporting of interventions hinders a robust quantitative understanding of behavioural intervention research in this subject area. Good co‐ordination of multidisciplinary care personnel could facilitate PA, by enabling a more comprehensive approach to targeting social cognitive processes. Well‐timed intervention and access to highly individualised PA support, including optional group PA classes, seem to also be important facilitators.